Kultur Kelas Menengah dan Kelahiran ICMI - Saiful Mujani (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1994)
Robert W. Hefner and Mitsuo Nakamura argue that the establishment of the Ikatan Cendikiawan Muslim se-Indonesia (ICMI), or the Muslim Intellectual Society of Indonesia, is a manifestation of the rising Muslim middle class that the cultural foundation of the Muslim middle class and the ICMI is 'renewal Islam' or Islamic neomodernism, which stresses the modern spirit: tolerant, pluralist, moderate, democratic, etc.DOI: 10.15408/sdi.v1i1.872